Impact of secondary barriers on CuIn1-xGaxSE2 solar-cell operation - Pudov, Alexei O., author; Sites, James R., advisor; Leisure, Bob, committee member; Eykholt, Richard, committee member; Wilmsen, Carl, committee member (Colorado State University. Libraries, 2005)
Thin-film solar cells based on CuInSe2 (CIS) absorber with a band gap of Eg = 1.0 eV and also based on CuIn1-xGaxSe2 (CIGS) alloy absorbers with a band-gap range of Eg = 1.0 - 1.67 eV are investigated in this work. Intermediate "buffer" semiconductor layers in p-n junctions of CIGS solar cells often improve photodiode properties of the devices. Several buffer-material selection criteria are discussed. The primary goal of the thesis is to study secondary barriers in the conduction band at the buffer/absorber interface, which may limit current transport and thus reduce the efficiency of the solar cells. The secondary goal is to explore potential benefits of alternative wide-band-gap buffers in CIGS cell structures. CIGS cells with standard CdS buffer layers, and alternative ZnS(O,OH) and InS(O,OH) buffer layers were studied. CdS/CuIn1-xGaxSe2 solar cells with variable Ga content have a range of conduction-and offsets (ΔEC) in the junction from moderately positive (spike offsets) in CdS/CuInSe2 to moderately negative (cliff offsets) in CdS/CuGaSe2. Large conduction-band spikes cause distortions in diode current-voltage (J-V) curves of solar cells. No CIGS-alloy forms a sufficient spike with CdS to create J-V distortions under regular white-light illumination. Even small spikes, however, can create substantial current-limiting barriers and cause J-V distortions in the dark or under "red" illumination when no photons with energy above the buffer band gap Eg(buffer) axe present. The higher barrier in this case is caused by the common heavy compensation of the buffer layer(s), such as CdS. These predictions were confirmed in experiments, in which the largest distortions in J-V measured under red light, also known as the "red kinks", were seen in CdS/CIS or low-Ga CdS/CIGS that have largest ΔEC, but the distortions were reduced for increasing Ga concentrations in the cells as the ΔEC decreased. The kinks were absent for cels above a certain critical Ga concentration, at which CdS/CIGS ΔEC is near zero. The corresponding value of Eg(CIGS) at that Ga concentration was near 1.2-1.3 eV. The value of the CIGS band gap correlates with white-light performance of these cells. It has been observed, earlier by others and also in this work, that CdS/CIGS cells with Eg(CIGS) above ~ 1.2 eV are limited in their open-circuit voltage Voc. Our results show additional evidence supporting an earlier study, which explained the Voc-limitation by increased recombination in structures with small-spike or cliff offsets, such as high-Ga CdS/CIGS. According to these results, the best buffer-material choice depends on Ga concentration in CIGS, since the buffer/absorber Ec-offset is important and it changes with Ga. Thus, it is unrealistic to expect a single buffer material to be the optimal match for the entire absorber-alloy range. CdS, for example, is a good buffer for CIGS with Eg ~ 1.1 - 1.2 eV. CuInSe2 is a good candidate for the absorber material in the bottom cells of thin-film solar-cell tandems. Since the bottom cells are exposed to practically only "red" photons, it is important that red-light J-V of CIS solar cells be distortion-free. It was shown that one approach to reduce secondary barriers in such cells is to thin the buffer layer(s). Experimental CdS/CIS cells with reduced CdS thickness demonstrated decreased amounts of red-light J-V distortion, and the thinnest-CdS (20-nm) ceils studied had little or no red kink. This principle was also confirmed on CIGS cells with alternative buffers. Sufficient flux intensity of blue photons (hv above Eg(buffer)) induces photoconductivity in the otherwise compensated buffers, which also results in lowering of the secondary barriers. In general, it was shown that CIGS cells with CdS, InS(O,OH), and ZnS(O,OH) buffers have a similar response to blue photons so that the J-V distortion, if present under red light, is reduced or entirely disappears with blue-light exposure. 'Blue' photons in each case are taken to mean energies above the buffer band gap. Buffers with different band gaps absorb different fractions of solar spectrum. Using wider-gap buffers, such as InS(O,OH) and ZnS(O,OH), was shown to produce higher photocurrents in solar cells. This photocurrent improvement is a central direction in the effort of further increasing efficiencies of thin-film solar cells. Reduced photon flux absorbed in the wide-gap buffer may result in slightly slower transition between the red-kink behavior and the normal diode J-V curve in the case when a substantial Ec-spike is present. In general, however, the solar cells with all studied buffer types showed relatively quick J-V recovery with exposure to the standard solar spectrum that contains blue photons, on the order of minutes, and relatively slow relaxation to the initial J-V kink without blue light, on the order of hours.
Keywords: condensation; energy; condensed matter physics